2007
DOI: 10.1021/pr070056t
|View full text |Cite|
|
Sign up to set email alerts
|

Method Development of Efficient Protein Extraction in Bone Tissue for Proteome Analysis

Abstract: Exploring bone proteome is an important and challenging task for understanding the mechanisms of physiological/pathological process of bone tissue. However, classical methods of protein extraction for soft tissues and cells are not applicable for bone tissue. Therefore, method development of efficient protein extraction is critical for bone proteome analysis. We found in this study that the protein extraction efficiency was improved significantly when bone tissue was demineralized by hydrochloric acid (HCl). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 49 publications
5
125
2
1
Order By: Relevance
“…However, they identified only 133 proteins, because they analyzed bone proteins using a one-step method without a demineralization stage. The other report showed only that bone proteins extracted from the skull bone of an adult beagle are carried using a demineralization step (23). There are no reports regarding the interaction between alveolar bone and soft tissue yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, they identified only 133 proteins, because they analyzed bone proteins using a one-step method without a demineralization stage. The other report showed only that bone proteins extracted from the skull bone of an adult beagle are carried using a demineralization step (23). There are no reports regarding the interaction between alveolar bone and soft tissue yet.…”
mentioning
confidence: 99%
“…This method was based on a recently reported sequential protein extraction protocol that was used to extract proteins from skull for comprehensive analysis of its proteome. Two-dimensional high-performance liquid chromatography-tandem mass spectrometry (LC-MS/ MS) was then applied to analyze the protein extracts, enabling the identification of 2479 proteins (23). We employed a similar method to extract and identify proteins in tooth alveolar bone.…”
mentioning
confidence: 99%
“…Nevertheless, classical single-solvent or parallel-solvents protein extraction methods are insufficient for proteome profiling and bioactivity study of velvet antlers due to the complexity of sample. In previous reports on proteome analysis of cartilage [10] and bone [11], the sequential protein extraction method improved significantly the number of identified proteins, suggesting that more proteins might be extracted if multiple complementary extraction buffers were sequentially used. In addition, many studies have demonstrated that the extracts of velvet antlers possessed widely biological activities [12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…Molecular techniques can be done by conducting the skeletal proteome analysis to evaluate the teratogenic effects on the foetal skeleton. Proteome analysis gives the information about mechanisms of physiological/pathological process in bone tissues [6]. This research was performed to examine the effect of the immature pineapple fruits extract on the occurrence of skeletal malformation and identify the protein profiles of skeleton on Balb-C foetal mice.…”
Section: Introductionmentioning
confidence: 99%